2016
DOI: 10.5194/hess-20-4867-2016
|View full text |Cite
|
Sign up to set email alerts
|

The Budyko functions under non-steady-state conditions

Abstract: Abstract. The Budyko functions relate the evaporation ratio E / P (E is evaporation and P precipitation) to the aridity index = E p / P (E p is potential evaporation) and are valid on long timescales under steady-state conditions. A new physically based formulation (noted as Moussa-Lhomme, ML) is proposed to extend the Budyko framework under non-steadystate conditions taking into account the change in terrestrial water storage S. The variation in storage amount S is taken as negative when withdrawn from the ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…dS/dt = 0) in these basins, affecting the calculations of E (Eq. 1) (Bring et al, 2015;Budyko, 1974;Moussa and Lhomme, 2016). We therefore applied the same bootstrapping and regression analysis to the 17 values and 10 mean values resulting from averaging the annual data of the period 1961-2012 into 3-and 5-year means, respectively.…”
Section: Regression Analysis Of the Residual Effect And Forest Attribmentioning
confidence: 99%
“…dS/dt = 0) in these basins, affecting the calculations of E (Eq. 1) (Bring et al, 2015;Budyko, 1974;Moussa and Lhomme, 2016). We therefore applied the same bootstrapping and regression analysis to the 17 values and 10 mean values resulting from averaging the annual data of the period 1961-2012 into 3-and 5-year means, respectively.…”
Section: Regression Analysis Of the Residual Effect And Forest Attribmentioning
confidence: 99%
“…Equation (6) constitutes the "Budyko picture" of ET in the "Budyko space", i.e., ET/P as a function of ET 0 /P and ∆S/P, while Equation (7) constitutes the "Turc picture" of ET in the "Turc space", i.e., ET/ET 0 as a function of P/ET 0 and ∆S/ET 0 [1,8]. In the present paper, only the Budyko picture will be utilized.…”
Section: The Homogeneity Postulatementioning
confidence: 99%
“…The present paper is a response to this challenge. It will be shown that, by making a single physically-relevant hypothesis about the functional relationship in Equation (4), the Budkyo framework can be extended to include changes in vadose-zone water storage in a manner broad enough to include all extant models [1,3,6] as special cases, while offering a rigorous approach to the specific modeling of Equation (4) that does not require adjustable parameters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations